Angina at Low heart rate And Risk of imminent Myocardial infarction (the ALARM study): a prospective, observational proof-of-concept study. Issue 1 (December 2015) - Wong, Yuk-ki; Stearn, Shelley; Moore, Sally; Hale, Beverley
Abstract Background Myocardial infarction (MI) is often preceded by unstable angina. Helping patients identify the onset of unstable angina rather than MI may result in earlier treatment and improve outcomes. Unstable angina is angina occurring at a lower-than-usual workload. Since heart rate (HR) is correlated with degree of exertion, we hypothesised that angina occurring at low HR is a warning signal for unstable angina and MI. Methods In this prospective study, 111 patients with acute coronary syndrome (ACS) or prognostically significant coronary disease were recruited. Each patient's HR was measured using a portable electrocardiogram (ECG) recorder after regular class III exercise on the Canadian Cardiovascular Society Angina Grading Scale and the cumulative moving average and three-sigma (standard deviation) range were calculated for each new measurement. The HR was subsequently measured at the beginning of angina; a HR lower than the preceding three-sigma ranges for class III or anginal HR was regarded as a 'warning signal'. The proportion of warning signals associated with ACS occurring in the following 2 weeks was compared with that for non-warning signals. Results Nine cases of ACS occurred in eight patients. Two cases were preceded by warning signals; a signal marked the onset of ACS in a third patient, and four patients failed to make anginal ECG recordings. There were 591 documented episodes of angina during the study and ECGs were available for 383 (64.8 %) of these of which 55 were warning signals. Of these warning signals, 4 occurred in the 2 weeks preceding ACS, compared with 4 of 328 non-warning signals (odds ratio, 6.4; 95 % confidence interval, 1.5–26.2;p  = 0.01; positive predictive value, 7.3 %; negative predictive value, 98.8 %). Conclusions Low HR angina may identify unstable angina and serve as an early warning for MI. In addition, angina that does not occur at a low heart rate indicates that ACS is very unlikely.